Practical Node-RED Programming : Learn powerful visual programming techniques and best practices for the web and IoT - Hagino, Taiji (Packt Publishing, 2021)
Use a low-code programming approach to create event-driven applications from scratch by wiring together hardware devices, APIs, and online services Key Features Discover how you can automate the Internet of Things (IoT) without writing huge blocks of code Learn how to wire together flows using a browser-based visual editor Handle IoT data with little to no coding knowledge Book Description Node-RED is a free and open source flow-based programming tool used to handle IoT data that allows programmers of any level to interconnect physical I/O, cloud-based systems, databases, and APIs to build web applications without code. Practical Node-RED Programming is a comprehensive introduction for anyone looking to get up to speed with the Node-RED ecosystem in no time. Complete with hands-on tutorials, projects, and self-assessment questions, this easy-to-follow guide will help you to become well versed in the foundations of Node-RED. You'll learn how to use Node-RED to handle IoT data and build web applications without having to write complex code. Once you've covered the basics, you'll explore various visual programming techniques and find out how to make sample flows as you cover web development, IoT development, and cloud service connections, and finally build useful real-world applications. By the end of this book, you'll have learned how to use Node-RED to develop a real-world application from scratch, which can then be implemented in your business. What you will learn Understand the history of Node-RED and why you need to learn a flow-based programming tool Use Node-RED to build Node.js-based applications Handle data for IoT devices using Node-RED flows Explore advanced Node-RED features such as connecting repositories and customizing the flow editor Find out what the MQTT protocol is and how it relates to Node-RED Create and publish your own nodes and flows using the Node-RED library Who this book is for This Node-RED book is for web developers and IoT engineers with some background in JavaScript and Node.js. Although not necessary, familiarity with the concepts of electronics will help you to make the most out of this book.